Jurisdiction Issues of the International Court and the effectiveness of ICJ's Decision in the Russia-Ukraine Dispute Resolution - Wulandari, Ria (Universitas Islam Negeri Raden Fatah Palembang, 2022)
In order for the Court to have jurisdiction over international issues, the disputing parties must accede to the Court's jurisdiction. Ukraine has independently brought its case before the International Court of Justice in its dispute with Russia. This calls into question both the Court's ability to resolve the issue and its own jurisdiction over it. Article 36, clauses 1-3, and article 41 of the Statute of the ICJ will be referenced in order to respond to these inquiries. This article uses a normative methodology. The research objective is to examine the effectiveness of the international court's decision. The method used in this research is normative. The approach method used is deductive. The research results show that the Court of International Justice does not have jurisdiction to issue a final decision but only has jurisdiction to issue a Provisional Measures. However this Provisional Measures will not be effective because the security council resolution as a means of forcing the implementation of the Provisional Measures will fail to be issued due to the Russian veto.